Radio QPO in the γ-ray-loud X-ray binary LS I +61°303. (28th July 2017) - Jaron, F.; Sharma, R.; Massi, M.; Fuhrmann, L.; Angelakis, E.; Myserlis, I.; Li, Guang-Xing; Shi, Xun
Abstract: LS I +61°303 is a γ-ray emitting X-ray binary with periodic radio outbursts with time-scales of one month. Previous observations have revealed microflares superimposed on these large outbursts with periods ranging from a few minutes to hours. This makes LS I +61°303, along with Cyg X-1, the only TeV emitting X-ray binary exhibiting radio microflares. To further investigate this microflaring activity in LS I +61°303 we observed the source with the 100-m Effelsberg radio telescope at 4.85, 8.35 and 10.45 GHz, and performed a timing analysis on the obtained data. Radio oscillations of 15 h time-scales are detected at all three frequencies. We also compare the spectral index evolution of radio data to that of the photon index of GeV data observed by Fermi -Large Area Telescope. We conclude that the observed Quasi Periodic Oscillations could result from multiple shocks in a jet.